2012
DOI: 10.1007/s00216-012-5772-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phosphatidylethanolamine molecular species in various food matrices by liquid chromatography–electrospray ionization–tandem mass spectrometry (LC–ESI–MS2)

Abstract: A liquid chromatographic-electrospray ionization-tandem mass spectrometric (LC-ESI-MS(2)) method has been developed for determination of the molecular species of phosphatidylethanolamine (PE) in four food matrices (soy, egg yolk, ox liver, and krill oil). The extraction and purification method consisted of a pressurized liquid extraction procedure for total lipid (TL) extraction, purification of phospholipids (PLs) by adsorption on a silica gel column, and separation of PL classes by semi-preparative normal-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Other authors (Zhou et al 2012b) analyzed the SM species in KO with LC-ESI-MS2, but they could not found any. The same authors in a different work reported the presence of eight different species of PE (Zhou et al 2012a). …”
Section: Phospholipid Molecular Speciesmentioning
confidence: 89%
“…Other authors (Zhou et al 2012b) analyzed the SM species in KO with LC-ESI-MS2, but they could not found any. The same authors in a different work reported the presence of eight different species of PE (Zhou et al 2012a). …”
Section: Phospholipid Molecular Speciesmentioning
confidence: 89%
“…Egg PE consists primarily of saturated FA such as stearic acid (18:0) at the sn -1 position, with a balanced mixture of unsaturated FA at the sn -2 position. The major PE molecular species include PE (16:0/18:1), PE (18:0/18:1), PE (18:0/18:2), and PE 18:0/20:4 [ 28 , 29 , 30 ]. Egg SM contains primarily saturated FA with palmitic acid (16:0) and stearic acid (18:0) making up ~80% of SM FA.…”
Section: Phospholipid Content and Composition Of The Chicken Eggmentioning
confidence: 99%
“…Mono- and di-unsaturated PE may influence cholesterol absorption like SM, as it has been shown to display a similar affinity to cholesterol as SM [ 49 , 50 ]. Both 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphoethanolamine (POPE) [ 49 ] and 1-stearoyl-2-linoleoyl- sn -glycero-3-phosphoethanolamine (SLPE) [ 50 ], major PE molecular species in egg yolk [ 30 ], have been shown to interact with cholesterol in monolayers to a similar degree as SM; this suggests an important role for PE in lipid raft formation at the inner membrane leaflet of cells where it is most abundant. Due to the high affinity for cholesterol observed with certain PE species, dietary PE from egg may influence the absorption of luminal cholesterol similar to dietary SM.…”
Section: Egg Phospholipids and Lipid Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the PL in krill oils, analytical methods based on liquid chromatography with tandem mass spectrometry can be used (Le Grandois et al, ; Zhou et al, , ). However, nuclear magnetic resonance (NMR) spectroscopy is of particular interest for the holistic quality control of PL and FA in krill oil (Burri et al, ).…”
Section: Introductionmentioning
confidence: 99%